Dependence of sustainability on country risk indicators in EU Baltic Sea region countries - Stankevičienė, Jelena; Sviderskė, Tatjana; Miečinskienė, Algita (Journal of Business Economics and Management, 2014)
Country risk and economic sustainability become more and more important in the contemporary economic world. This paper proposes the analysis on relationship between country risk and economic sustainability in EU Baltic Sea region countries, based on statistical data of the year 2012. Investigations and calculations of rankings for country risk and sustainability were made and the results were optimized by implementing MOORA (Multi-Objective Optimization by Ratio analysis) and MULTIMOORA (MOORA plus Full Multiplicative Form) methods. Furthermore, correlation analysis was prepared and the informative results were obtained. Starting with a system of 8 alternative responses on 21 objectives (indicators), from several approaches the unambiguous results were obtained, which could be engaged in the process of creating new model for country risk assessment and its dependent sustainability indicators for EU Baltic Sea region countries.